2012
DOI: 10.4172/2161-0932.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Renal Volume and Fetal Doppler in Normal and Growth Restricted Fetuses: Is there a Correlation?

Abstract: Objective: To evaluate if umbilical, middle cerebral and fetal renal artery Doppler could affect fetal kidney volume in healthy and growth restricted fetuses after 26 weeks of gestation. Design: A prospective cross sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 22 publications
11
8
0
Order By: Relevance
“…The renal artery PI was 0.79 and 1.75, respectively, in normally growing foetuses and growth restricted foetuses; and there was a statically significant correlation between these two groups [13]. They also detected a negative correlation between the foetal arterial pO2 and AFI.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The renal artery PI was 0.79 and 1.75, respectively, in normally growing foetuses and growth restricted foetuses; and there was a statically significant correlation between these two groups [13]. They also detected a negative correlation between the foetal arterial pO2 and AFI.…”
Section: Discussionmentioning
confidence: 90%
“…One-hundred foetuses were evaluated by Behery and colleagues [13] with colour Doppler US between the gestational weeks 26-34, and forty-three of them had growth retardation. Renal artery PIs were detected at 0.79 and 1.75, respectively, in normally growing foetuses and growth restricted foetuses, and there were statically significant correlations between these two groups [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our research, there was no statistically significant difference between the two groups with regard to the length of the right and left kidneys, however a significant difference in width, which was the same findings as previously reported, is also in line with previous study, which showed that in small-for-gestational age fetuses the length of the kidney remained largely unchanged. In addition, renal duration is a weak measure of the amount of renal parenchyma relative to the volume of the renal parenchyma [13].…”
Section: Discussionmentioning
confidence: 99%
“…6 Many authors, in their study did not find significant difference in kidney length between normal and growth restricted fetuses, but they observed decreased kidney volume (29% less) in foetuses with intrauterine growth restriction than that of normally grown foetuses, which may be due to impaired nephrogenesis as a result of decreased renal perfusion. 3,14,15 But Indu Kaul et al (2012). 16 found in their study the mean Left fetal kidney length was slightly but significantly longer than the mean Right at each gestational period, which was also observed by Fitzsimons RB et al, 17 Duval JM et al 18 and Sampaio FJ et al, 19 as mentioned by Indu Kaul et al…”
Section: Discussionmentioning
confidence: 99%